Postcolonial Pharmakon: Traumatic Transmission in Tony Perez's Cubao-Kalaw Kalaw-Cubao - Ku, Ryan (Archīum Ateneo, 2024)
Tracing Tony Perez’s Filipino modernism in Cubao–Kalaw Kalaw–Cubao to trauma, this article considers whether the novel’s processing of psychic trauma also amounts to the processing of national trauma. Seemingly positing representation as the means of traumatic processing, Perez, in distinguishing the unconscious transmission of the traumatic event from the conscious narration of its aftereffects, in fact premises representation on deconstruction. Consisting in the displaced and deferred repetition, or writing, of trauma, this process is facilitated in the novel by three discursive practices—Catholicism, psychotherapy, and creative writing—that are derived from the colonial history of the Philippines. Rather than corresponding to the nation’s postcolonial trauma, psychic trauma in the novel is thus processed through the remainders of national trauma. Of these postcolonial legacies that serve as psychic cures, Perez privileges one that causes him to disavow not only the others but also kapwa, the indigenous concept of sociality recuperated by sikolohiyang Pilipino (Filipino psychology) after independence to counter colonial history. Rather than working through national trauma with psychic trauma, Perez ultimately overcomes psychic trauma through the disavowal and repetition of national trauma, thus potentially inducing further psychic trauma.